Mass transfer kinetics and regressional‐desirability optimisation during osmotic dehydration of pumpkin, kiwi and pear - Arballo, Javier Ramiro (2011)
Mass transfer kinetics and optimisation of osmotic dehydration (OD) of fruits and vegetables with diverse structures were studied. Different concentrations of sucrose (20–60 Brix) and process times (0–24 h) were used. Magee’s model was appropriate for predicting water loss (WL), while Azuara’s model fitted well solids gain (SG) data and represented more accurately the evolution of the complete process close to equilibrium. Polynomial equations for each kinetic variable [WL, SG and weight reduction (WR) – for pumpkin, kiwi and pear] using multiple linear regression were fitted for a selected range of experimental data (30–240 min, 20–60 Brix). A complete solution algorithm for desirability function was coded in Matlab 7.2 (Mathworks, Natick, MA, USA) with the aim to optimise osmotic dehydration process in terms of WL, SG and WR; optimal conditions were found for each fruit. Besides, an optimal common zone was identified for OD corresponding to process time from 114 to 240 min and sucrose concentration from 54 to 60 Brix.